In-house Validation of Accelerated Solvent Extraction-High Performance Liquid Chromatographic Method for Determination of Polycyclic Aromatic Hydrocarbons in Portuguese Sewage Sludge. (2nd January 2021) - Antunes, Patrícia; Rodrigues, Alexandre; Neto, Ana; Cardoso, Vitor Vale; Benoliel, Maria João; Almeida, Cristina Maria Martins
Abstract: The application of sewage sludge in agricultural field should be done carefully to prevent any form of adverse environmental impact or food safety problems. Maintaining a high quality of soil is essential for a high quality agricultural products. Therefore, the monitoring of sewage sludge before their application is mandatory. Accelerated solvent extraction (ASE) coupled to the high performance liquid chromatography with fluorescence and diode array detector (HPLC–FLD–DAD) was optimized and validated for the analysis of 16 polycyclic aromatic hydrocarbons (PAH) in sewage sludge samples. The optimized conditions were obtained using dichloromethane, flow mode, one static cycle with 5 minutes, washed sea sand as dispersant agent and a flow of 1.0 mL/min at 100 °C. The method detection limit (MDL) and method quantification limit (MQL) for the sum of 16 PAHs were 1.9 μg/kg and 6.3 μg/kg, in dry matter, respectively. The uncertainty of the method (ASE-HPLC–FLD–DAD) was also estimated. The total concentration of PAHs varied between 0.103 mg/kg d.m. and 23.5 mg/kg d.m. Twenty-five sewage sludge samples from wastewater treatment plant (WWTP) were analyzed, only one sludge sample showed PAHs concentrations above the legal limit of 6 mg/kg in dry matter, and it cannot be used as soil fertilizer.